2023
DOI: 10.1001/jama.2023.24391
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Noninvasive Airway Management of Comatose Patients With Acute Poisoning

Yonathan Freund,
Damien Viglino,
Marine Cachanado
et al.

Abstract: ImportanceTracheal intubation is recommended for coma patients and those with severe brain injury, but its use in patients with decreased levels of consciousness from acute poisoning is uncertain.ObjectiveTo determine the effect of intubation withholding vs routine practice on clinical outcomes of comatose patients with acute poisoning and a Glasgow Coma Scale score less than 9.Design, Setting, and ParticipantsThis was a multicenter, randomized trial conducted in 20 emergency departments and 1 intensive care u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…3 Furthermore, assigning a GCS score involves some subjective judgment, which may lead to interobserver variability. 4 The percentage agreement for GCS scoring among physicians was not reported in this study, 1 which could lead to potential misclassification of patients in this study.…”
Section: Noninvasive Airway Management Of Comatose Patients With Acut...mentioning
confidence: 67%
See 3 more Smart Citations
“…3 Furthermore, assigning a GCS score involves some subjective judgment, which may lead to interobserver variability. 4 The percentage agreement for GCS scoring among physicians was not reported in this study, 1 which could lead to potential misclassification of patients in this study.…”
Section: Noninvasive Airway Management Of Comatose Patients With Acut...mentioning
confidence: 67%
“…The clinical benefit reported for the primary outcome was driven by a reduced intensive care unit (ICU) admission rate and consequently shorter ICU length of stay in the intervention group. 1,2 Given that patients receiving intubation typically require ICU care, the study's design inevitably resulted in shorter ICU stays for the intervention group. This finding, therefore, does not justify avoiding intubation of intoxicated patients.…”
Section: Noninvasive Airway Management Of Comatose Patients With Acut...mentioning
confidence: 99%
See 2 more Smart Citations
“…The Non-Invasive Airway Management of Comatose Poisoned Emergency Patients (NICO) randomized controlled pragmatic clinical trial reported that withholding intubation in poisoned patients with GCS ≤ 8 was safe, and was associated with clinical improvement in a composite hierarchical endpoint of death, ICU stay, and hospital stay [5]. Notably, there were no deaths in the study.…”
mentioning
confidence: 99%